Microwave Assisted Synthesis of New Adamantyltriazine Derivatives - Al-Qawasmeh, Raed A.; A. Salameh, Bader; AlRazim, Rami; A. AlDamen, Murad; Voelter, Wolfgang (Letters in Organic Chemistry, 2014)
The synthesis of new 2-adamantyl-1,2,4-triazine derivatives is described utilizing both, conventional and microwave methods and were obtained in good yields. The proposed structures of the adamantyltriazines were characterized using MS, 1H NMR and 13C NMR spectral data and confirmed by determination of X-ray structure for 9c.
Keywords: organic synthesis